Experimentation as intersection between composition and performance in musical creation: a collaborative experience (Orfeu, 2020)
The article discusses the role of experimentation in the creative collaboration ‒ composition and performance ‒ of the group Coletivo N·S·L·O. The investigation builds on records collected during the creative process and reports produced by the members themselves. Thus, the discussion considers the particular perspectives of each one, until the consolidation of the musical products. In this process, experimentation creates a space in which the composer and performers act together in a decisive way for the creative result achieved. The results of the experiments are incorporated into the composition, through indeterminacy, and performance preparation, through games, consisting of musical materials, actions and interactions. Collaboration, while preserving the division of roles, is horizontal and flexible. The aesthetic proposal encompasses the aspects of theatricality and play, as a result of the dynamics between indeterminate notation and performance.
Keywords: Musical creation; collaboration; indeterminacy; experimentation; creative process